Pengaruh Kekuatan Otot Lengan dan Kekuatan Otot Perut terhadap Performa Kecepatan Renang 50 Meter Gaya Bebas - Moh Zainuddin; Mokhamad Nur Bawono; Heri Wahyudi; Roy Januardi Irawan (Mutiara Pendidikan dan Olahraga, 2026)
The 50 meter freestyle is a sprint event that requires explosive strength, efficient technique, and optimal body stability. Arm muscle strength contributes directly to propulsion, while core muscle strength supports stability and force transfer. This study aimed to analyze the influence of arm and abdominal muscle strength on 50-meter freestyle swimming performance among athletes of the Science Swimming Team (SST) Sidoarjo. A quantitative correlational design was employed with a sample of 10 athletes aged 10–12 years (5 males, 5 females). Arm muscle strength was measured using the pull-up test, abdominal strength with a 30-second sit-up test, and swimming performance with the best time in a 50-meter freestyle trial. Data were analyzed using Spearman correlation and multiple linear regression with a 0.05 significance level. Results indicated a significant correlation between arm strength and swimming performance (r = 0.773; p = 0.009), while abdominal strength showed a positive but non-significant correlation (r = 0.609; p = 0.062). Regression analysis revealed that both variables together explained 57.7% of the variance in swimming speed. It is concluded that arm muscle strength has a dominant influence on freestyle sprint performance, whereas core muscles serve as supporting factors for stability and efficiency. These findings highlight the importance of integrated training programs combining arm and core strengthening to optimize sprint performance in young swimmers.